O curso de Biblioteconomia e Documentação da Universidade Federal de Sergipe (2008-2017): criação, implantação e funcionamento - Souza, Salim Silva (2019)
This study has as general objective to analyze the historical trajectory of the Library and Documentation Course created at the Federal University of Sergipe, examining its process of creation, implementation and operation in the scenario of higher education in Sergipe. It was defined as initial time frame 2008, year that was presented the project for the creation of the course and final 2017, year that begins the first professional master's degree in Information and Knowledge Management. This study is justified by its pioneering character in the area of the history of Librarianship in the State, and by its contribution in the study of the history of Sergipe higher education. The aim was to explore the potential of qualitative research, presenting the Oral History methodology as a way to contribute to the construction of the thinking about the object of study, through the experiences of the graduates, teachers and former teachers of the course, as well as their founders, extracted through interviews. Various documents were gathered, such as minutes of the Departmental Council of the Library and Documentation course, the DCI Structuring Teaching Nucleus and the Collegiate Council of the Center for Applied Social Sciences, as well as the Pedagogical Project of the Course, Portarias and Offices relevant to the proposed theme by means of visits to the UFS Central Archive, the Secretariat of the Information Sciences Department, the UFS Central Library and the Teaching Methods and Techniques Division of the UFS Graduate Degrees Office (DIMET). In order to guide this study, we sought support in Cultural History, which works on the concepts of Memory and Document (LE GOFF, 2001, 2003), Collective Representation (CHARTIER, 1988), Intellectual Field (BOURDIEU, 1996) and Intellectual Engaged (SIRINELLI, 1996). This research is also guided by the Microhistory approach (LEVI, 1992). This research will contribute to the studies on History of Higher Education in Sergipe, especially the Federal University of Sergipe.